Overview of the risk assessments for hydrogen refuelling stations in Japan - Tomoya Suzuki; Kento Shiota; Jo Nakayama; Yuichiro Izato; Atsumi Miyake (Chemical Engineering Transactions, 2022)
Hydrogen refuelling stations (HRSs) have attracted widespread attention in Japan. The Ministry of Economy, Trade, and Industry in Japan set a goal for the construction of HRSs in a strategic roadmap. Owing to the explosive and fire hazards associated with HRSs, a considerable amount of safety studies for HRSs has been conducted for several years; however, the safety studies conducted in Japan are yet to be reviewed. This study aimed to comprehensively review the safety studies conducted in Japan, particularly the risk assessment (RA) of HRSs, and to provide useful insights on the direction of future studies on the safety of HRSs. To this end, a comprehensive review of international and Japanese safety studies for HRSs was presented by adopting a bibliometric analysis approach and an overview of Japanese safety studies for HRSs was presented based on the type of HRSs. The results revealed that it is essential to conduct the RA of HRSs, particularly for HRSs yet to be assessed, to contribute to the decision-making process for the social implementation of HRSs in the future.